The Influence of Political Communication on TikTok on Gen Z's Support in the 2024 Election - Dewi, Nevy Rusmarina (JPW (Jurnal Politik Walisongo), 2025)
Every election always brings up new strategic ideas and media as used. Likewise in the 2024 Election, new media will emerge using the latest social media such as: Tik Tok, Instagram, and Twitter as a means of political communication. All presidential candidates pairs utilize social media and use new strategies in political campaigns to gain the most votes. The purpose of this study is to find out how Tik Tok becomes a new and effective politicalcommunication media in the process of conveying political messages. In addition, it is also to find out to what extent the influence of Tik Tok content on Generation Z and millennials can influence their political decisions in participating in the Election. This study uses a qualitative research method with a library study. The results of this study reveal that Tik Tok is the main target of political campaigns because almost all of the young generation who are the main voters in their elections use the application in their daily lives, thus giving rise to a strategy to attract the sympathy of the younger generation through interesting content that is uploaded. In addition, the younger generation is easily influenced by content that is packaged according to their movements and thought patterns so that it can influence their political decisions.